2022
DOI: 10.3389/fnagi.2021.815439
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Genotype Moderation of the Association Between Physical Activity and Brain Health. A Systematic Review and Meta-Analysis

Abstract: IntroductionPossession of one or two e4 alleles of the apolipoprotein E (APOE) gene is associated with cognitive decline and dementia risk. Some evidence suggests that physical activity may benefit carriers of the e4 allele differently.MethodWe conducted a systematic review and meta-analysis of studies which assessed APOE differences in the association between physical activity and: lipid profile, Alzheimer's disease pathology, brain structure and brain function in healthy adults. Searches were carried out in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 97 publications
0
3
3
Order By: Relevance
“…Relatedly, it is possible that the APOE ε4 carrier and non-carrier groups included in the two studies differed in known but unobserved moderators of the allele's effect. Relevant factors include obesity ( Mole et al, 2020 ), physical activity ( Pearce et al, 2022 ), diet ( Yassine and Finch, 2020 ), and bilingualism ( Vila-Castelar et al, 2022 ), none of which were reported here or by Hodgetts et al This might at least partly explain why we failed to replicate the effect originally reported by Hodgetts et al, although future well-powered prospective studies are needed to evaluate the extent to which such factors moderate APOE ε4's purported effect on brain structure early in life.…”
Section: Discussioncontrasting
confidence: 51%
“…Relatedly, it is possible that the APOE ε4 carrier and non-carrier groups included in the two studies differed in known but unobserved moderators of the allele's effect. Relevant factors include obesity ( Mole et al, 2020 ), physical activity ( Pearce et al, 2022 ), diet ( Yassine and Finch, 2020 ), and bilingualism ( Vila-Castelar et al, 2022 ), none of which were reported here or by Hodgetts et al This might at least partly explain why we failed to replicate the effect originally reported by Hodgetts et al, although future well-powered prospective studies are needed to evaluate the extent to which such factors moderate APOE ε4's purported effect on brain structure early in life.…”
Section: Discussioncontrasting
confidence: 51%
“…30 The current findings are, however, in line with a recent meta-analysis of eight studies that also used PET Aβ measures and MET score as a PA measurement. 48 Of interest, the current study findings did not align with prior work from the AIBL study where the PA and Aβ association was noted in APOE ε4 carriers. To put the current findings into context, the data used by Brown et al 15 was smaller in number (n = 116) due to the study's duration to that point.…”
Section: Discussioncontrasting
confidence: 95%
“…Previous studies have investigated the moderating impact of APOE ε4 allele status on the relationship between PA and Aβ, with mixed results 30 . The current findings are, however, in line with a recent meta‐analysis of eight studies that also used PET Aβ measures and MET score as a PA measurement 48 . Of interest, the current study findings did not align with prior work from the AIBL study where the PA and Aβ association was noted in APOE ε4 carriers.…”
Section: Discussioncontrasting
confidence: 63%
“…APOE ε4 is a mediator of numerous pathological processes related to AD risk. APOE increases tau hyperphosphorylation, yet APOE ε4 carriers and non-carriers show similar benefits to brain health as a result of engagement in physical activity ( Pearce et al, 2022 ). Given physical activity engagement entails a suite of biological processes, it is likely that many of these molecular targets align with AD neuropathology and therefore require further investigation ( de Frutos Lucas et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%